Investigating the sigma formation in homogenization treatment of the 309L stainless cast billet - Hung-Yang Chu; Min-Chang Wu; Ren-Kae Shiue; Sheng-Yuan Cheng (Journal of Materials Research and Technology)
309L is a low-carbon (0.03 wt% max) and high-alloy austenitic stainless steel, which is particularly valued for the welding filler wire application. The 309L cast billet is commonly used to produce ultra-fine welding filler wire. However, the δ ferrite in the cast 309L is unstable at elevated temperatures and may transform into the deleterious sigma phase. The morphology, distribution, and volume fraction of the sigma and δ ferrite in the cast 309L billet affects the yield of the following hot and cold wire drawing processes. This study explores the microstructural evolution of the 309L cast billet subjected to various homogenization heat treatments. Microstructures of the as-cast 309L are not uniform along its radial direction due to different cooling rates in casting. The homogenization of the cast 309L at 1240 °C for 2h can slightly spheroidize the morphology of δ ferrite. Further increasing the homogenization time to 6 h demonstrates the best spheroid effect of the δ ferrite and sigma in the cast 309L specimen. The sigma phase is hard and brittle. Delamination of the sigma/austenite and sigma/δ ferrite interfaces was found after the microhardness test. The presence of the sigma phase is detrimental to the following hot and cold wire drawings of the cast 309L. The sigma formation in the 309L cast billet is strongly related to the cooling rate after homogenization at 1240 °C. Rapid air cooling must be applied at temperatures between 600 and 850 °C to avoid the sigma formation.